The Evolution of Subsidies Received by Dairy Farms in the Visegrad Group Countries in the 2015-2019. Based on FADN Data - Vajdáné Szabó, Ildikó; Hegedűsné Baranyai, Nóra (Acta Carolus Robertus, 2022)
This study examines the dairy farms in the countries of the Visegrad Group and looks at how farms in each country were able to take advantage of the opportunities offered by subsidies for investment and current operation in the 5 years after the end of the milk quota (2015-2019). During the period under review, the dairy cow stock declined in Hungary, the Czech Republic and Slovakia, although the first two countries experienced some recovery after 2018. In Poland, the stock increased slightly between 2015 and 2019. Slovakia and the Czech Republic have the highest livestock concentrations, while Poland’s dairy production is characterized by a structure based on small family farms. The highest milk yield per cow is in Hungary and the Czech Republic, followed by Slovakia. The higher performance is the result of modern feed and better genetic potential. It is in Slovakia where farmers’ tax burdens are the biggest. Negotiations to reduce these started in 2021-22, but no concrete results have been achieved yet. Concerning the investment and all the other types of subsidies, the Czech and the Slovak farmers were in the most favorable situation; the Czech farmers received the highest amounts of investment subsidies, while their Slovak counterparts received the highest amounts of subsidies for current production. Poland did not directly support dairy production, but rather wanted to encourage farmers to develop the beef cattle stock rather than dairy production.